Hubungan Antara Kredibilitas Pembicara Program Edukasi Investasi Saham Dengan Sikap Pegawai Terhadap Saham Perusahaan - Hafizhah Zuhri; Iriana Bakti; Kokom Komariah (Lembaga Pengembangan Kinerja Dosen, 2024)
The aim of this research is to determine the extent of the relationship between the credibility of speakers in stock investment education programs and employee attitudes towards company shares. This research uses Source Credibility theory. The method used is the Correlational Method, through the Spearman Rank (rs) hypothesis test with descriptive and inferential analysis techniques. The respondents for this research were 64 people who were selected based on simple random sampling techniques. The data collection techniques used were questionnaires, interviews and literature study. The results of this research show that the credibility of the stock investment education program speaker has a strong relationship with employee attitudes with an rs coefficient of 0.638 and a sig of 0.001 < 0.05. This is caused by the speaker's trustworthiness, the speaker's expertise, and the speaker's positive appeal and is related to changes in employee attitudes. The conclusions of this research show that the speaker's trustworthiness with employees' opinions, perceptions, affective and actions has a moderate relationship, the speaker's expertise with employees' opinions, perceptions, affective and actions has a moderate relationship, and the speaker's attractiveness with opinions, perceptions, affective , and employee actions have a strong relationship.